2017
DOI: 10.1002/acp.3325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Integrating Physical Activities Into a Science Lesson on Preschool Children's Learning and Enjoyment

Abstract: This study investigated the effects of physical activities that were integrated into a science lesson on learning among preschool children. A total of 90 children from seven childcare centres (M age = 4.90, SD = 0.52; 45 girls) were randomly assigned across an integrated physical activity condition including task-relevant physical activities, a nonintegrated physical activity condition involving task-irrelevant physical activities, or a control condition involving the predominantly conventional sedentary style… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 76 publications
7
73
0
3
Order By: Relevance
“…The program components (delivery and content) were well-received by teachers and students, showing the program's feasibility and potential sustainability for introducing movement-based English lessons in primary school students, and their potential to become part of the regular practice. Importantly, the post-program evaluation questionnaire revealed that children rated the program as very enjoyable, consistent with evidence from other studies that students consider integrating physical activity an enjoyable teaching method of several learning domains [83][84][85][86][87][88] .…”
Section: Educational Implicationssupporting
confidence: 86%
“…The program components (delivery and content) were well-received by teachers and students, showing the program's feasibility and potential sustainability for introducing movement-based English lessons in primary school students, and their potential to become part of the regular practice. Importantly, the post-program evaluation questionnaire revealed that children rated the program as very enjoyable, consistent with evidence from other studies that students consider integrating physical activity an enjoyable teaching method of several learning domains [83][84][85][86][87][88] .…”
Section: Educational Implicationssupporting
confidence: 86%
“…This finding suggests that single bouts of physical activity at lower intensities may offer similar attentional enhancements to those observed following higher intensities (ie, moderate-to-vigorous), which are widely supported in the extant acute physical activity and classroom activity break literature. 4,10 Importantly, the physically active instruction intervention in the present study resulted in a greater duration (ie, seven more minutes of physical activity) of physical activity at higher intensity (low-to-moderate) relative to other physically active learning interventions in preschoolers 11,12,14 ; and future research may seek to integrate similar activities to increase the likelihood that children accrue the many health-related benefits associated with greater amounts of moderate-to-vigorous activity during lessons. Taken together, the findings suggest that physically active instruction improves on-task behavior and reduces the time spent sedentary.…”
Section: Discussionmentioning
confidence: 78%
“…Findings from the present investigation are consistent with the notion that physically active lessons create a substantive change in physical activity by reducing sedentary behavior. 5,[11][12][13][14] Mahar and colleagues 5 observed that school-aged children who engaged in the energizers' classroom-based physically active lessons accumulated almost 800 additional steps over the course of an entire school day relative to students engaged in conventional lessons. Mavilidi and colleagues 14 integrated movement with number knowledge, which resulted in preschoolers accruing about 2 minutes of moderate-to-vigorous activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intervention length ranged from one-off sessions [48][49][50][51][52] to three years 39 44 53 54 . Of studies providing physically active lessons on multiple occasions, total weekly intervention duration ranged from 10 minutes 55 to 180 minutes a day 56 . Only two studies were explicitly based on theory, namely the COM-B model of behaviour change 18 37 .…”
Section: Study Selectionmentioning
confidence: 99%